Incidence, Risk Factors and Post-Operative Outcome of Cesarean Hysterectomy Among Placenta Previa Patients at a Tertiary Hospital (Journal of Rangpur Medical College, 2025)
Introduction: Placenta previa remains a significant obstetric complication associated with maternal morbidity, particularly when coupled with abnormal placentation and previous cesarean deliveries. Objective: This study aimed to assess the incidence, risk factors, and postoperative outcomes of cesarean hysterectomy among placenta previa patients at a tertiary hospital in Bangladesh. Methods: The cross-sectional observational study was conducted in the Department of Obstetrics and Gynaecology at Dhaka Medical College and Hospital, over a period of six months, from July 2017 to December 2017, including 50 pregnant women with confirmed placenta previa. Results: Cesarean hysterectomy was required in 20% of placenta previa cases, predominantly among patients with central placenta previa and prior cesarean deliveries. Multiparity, irregular or absent antenatal care, and a history of uterine curettage were prominent risk factors. Postoperative complications occurred in 50% of hysterectomy cases. Despite a high live birth rate (90%), 30% of newborns had low birth weight, and 24% required NICU admission. Conclusion: Cesarean hysterectomy remains a vital but high-risk intervention in managing complicated placenta previa. Early identification of high-risk patients, rational use of cesarean sections, and coordinated multidisciplinary care are essential to reduce maternal and perinatal complications.J Rang Med Col. 2025 Sep;10(2): 84-89